Functional near-infrared spectroscopy as a diagnostic aid for stable schizophrenia - Zhang, Suzhen; Li, Ting; Chen, Liangliang; Cong, Tongkuai; Kuai, Xinping; Mu, Yonggang (Frontiers in Psychiatry, 2025)
ObjectiveCognitive impairment in schizophrenia (SCZ) is common, but the mechanism remains unclear. This study aimed to investigate whether brain activation during the functional near−infrared spectroscopy (fNIRS) verbal fluency test (VFT) task is associated with cognitive deficits and to evaluate the reliability of fNIRS as a clinical tool for diagnosing stable SCZ.MethodsA total of 45 stable SCZ patients and 30 healthy controls (HC) were included. Demographic information, Positive and Negative Symptom Scale (PANSS), and MATRICS Consensus Cognitive Battery (MCCB) were assessed. During VFT, hemodynamic responses in the frontotemporal cortex were monitored with fNIRS.ResultsDuring VFT, individuals with SCZ demonstrated a reduced number of valid words, lower β value in channel 8, 25-26, 35–36 and 47-48, and decreased integral value (IV) in both the prefrontal lobe and bilateral temporal lobes. IV of the temporal lobes and the β value of channel 48 demonstrated sensitivity for diagnosis of SCZ, with an area under the receiver operating characteristic curve of 0.781 (95% CI: 0.667-0.896), and 0.762 (95% CI: 0.655-0.869), respectively. Moreover, IV of the temporal lobes correlated positively with multi-domain of cognition, including speed of processing, attention/vigilance, social cognition and MCCB total scores. The β value of channel 48 correlated positively with speed of processing.ConclusionOur findings suggest that fNIRS may serve as a valuable clinical measure of cognition assessment, and IV of bilateral temporal lobes and β value of channel 48 can be used as candidate biomarkers to differentiate individuals with schizophrenia.